Cell wall physicochemical aspects of nectarine fruit related to flesh reddening symptoms - Mignani, Ilaria; Vasilakakis, Miltiadis; Manganaris, George A. (My University, 2006)
Flesh reddening (FR) symptoms are developed in many nectarine cultivars, without however having dissected its cell wall physicochemical aspects. ‘Caldesi 2000’ is a very susceptible nectarine to FR and was used as model cultivar in the current study. Two lots of 30 fruits were allowed to ripen for 5 d (shelf life) at 20°C either after harvest or after 4-week cold storage and the fruits with either white or reddish flesh surface were selected for cell wall analysis. Fruits with FR symptoms were characterized by a lower content of uronic acid in the insoluble pectin fraction, and therefore a lower proportion of uronic acid in the insoluble to water-soluble pectin fraction. The decrease of neutral sugar content was mainly attributed to cold storage. However, the fruits with FR symptoms were characterized by a lower content of total neutral sugars. Additionally, significant differences in glucose content were monitored between the white flesh fruits and the fruits with FR symptoms. The nectarine fruits subjected to cold storage were characterized by a decreased cellulose content, whereas the decrease was more intense in nectarines with FR symptoms.
Keywords: Pectin; Fruits; Uronic acids; Cellulose